2022
DOI: 10.1007/s00330-022-08631-8
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis improves tumour size measurement on computed tomography in pancreatic ductal adenocarcinoma: comparison with gross pathology and multi-parametric MRI

Abstract: Objectives Tumour size measurement is pivotal for staging and stratifying patients with pancreatic ductal adenocarcinoma (PDA). However, computed tomography (CT) frequently underestimates tumour size due to insufficient depiction of the tumour rim. CT-derived fractal dimension (FD) maps might help to visualise perfusion chaos, thus allowing more realistic size measurement. Methods In 46 patients with histology-proven PDA, we compared tumour size measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…A recent study revealed that fractal analysis that allows differentiating between viable tumour and dense fibrosis at the periphery of PDAC improves PDAC size estimates. 19 Our study has some limitations. First, the retrospective design has assumably introduced some inclusion biases.…”
Section: à25mentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study revealed that fractal analysis that allows differentiating between viable tumour and dense fibrosis at the periphery of PDAC improves PDAC size estimates. 19 Our study has some limitations. First, the retrospective design has assumably introduced some inclusion biases.…”
Section: à25mentioning
confidence: 89%
“…A recent study revealed that fractal analysis that allows differentiating between viable tumour and dense fibrosis at the periphery of PDAC improves PDAC size estimates. 19…”
Section: Discussionmentioning
confidence: 99%
“…Although high-resolution imaging modalities can depict heterogeneity with smaller voxel size than MRE, their intrinsic sensitivity to biophysical tissue properties and their alterations in cancer is often unclear. For example, CT frequently underestimates tumor size due to insufficient sensitivity to small vessels in the rim 118 . By contrast, MRE stiffness of PDAC provides a contrast that reveals tumor boundaries to the naked eye without the need for contrast agent administration 77 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CT frequently underestimates tumor size due to insufficient sensitivity to small vessels in the rim. 118 By contrast, MRE stiffness of PDAC provides a contrast that reveals tumor boundaries to the naked eye without the need for contrast agent administration. 77 However, the large heterogeneity of mechanical structures depicted by MRE in brain tumors poses challenges to the quantification of values and tabulation of thresholds for tumor characterization.…”
Section: Hypothesis Of Tissue Fluidity In Cancer Measured By In Vivo Mrementioning
confidence: 99%
“…In [25] it was demonstrated that "fractal analysis is a suitable method for quantifying perfusion heterogeneity." In [26] it was established for one type of pancreatic cancer that "fractal analysis visualizes perfusion chaos in the tumor rim and improves size measurement on CT in comparison to" other methods. Thus, more accurate CT reconstruction of rough shapes may lead to better detection and a more accurate assessment of tumors.…”
Section: 2mentioning
confidence: 99%